Fusion of auditory inspired amplitude modulation spectrum and cepstral features for whispered and normal speech speaker verification. (September 2017) - Sarria-Paja, Milton; Falk, Tiago H.
Highlights: Speaker verification based on whispered speech while keeping performance for normal speech. Three innovative features carrying invariant information for both speaking styles. A score fusion scheme to show the complementarity of the proposed feature sets. A new approach to extract discriminative features from modulation spectrum signal representation. Abstract: Whispered speech is a natural speaking style that despite its reduced perceptibility, still contains relevant information regarding the intended message (i.e., intelligibility), as well as the speaker identity and gender. Given the acoustic differences between whispered and normally-phonated speech, however, speech applications trained on the latter but tested with the former exhibit unacceptable performance levels. Within an automated speaker verification task, previous research has shown that i) conventional features (e.g., mel-frequency cepstral coefficients, MFCCs) do not convey sufficient speaker discrimination cues across the two vocal efforts, and ii) multi-condition training, while improving the performance for whispered speech, tends to deteriorate the performance for normal speech. In this paper, we aim to tackle both shortcomings by proposing three innovative features, which when fused at the score level, are shown to result in reliable results for both normal and whispered speech. Overall, relative improvements of 66% and 63% are obtained for whispered and normal speech, respectively, over a baseline system based on MFCCs and multi-condition training.